Long-Term immunopersistence and safety of the Escherichia coli-produced HPV-16/18 bivalent vaccine in Chinese adolescent girls - Xingmei Yao; Wengang He; Xianghong Wu; Jianxiang Gu; Jing Zhang; Bizhen Lin; Zhaofeng Bi; Yingying Su; Shoujie Huang; Yuemei Hu; Ting Wu; Jun Zhang; et al. (Human Vaccines & Immunotherapeutics, 2022)
The study assessed long-term immunopersistence and safety of the Escherichia coli (E. coli)-produced HPV-16/18 bivalent vaccine. In total, 979 participants in the initial immunogenicity noninferiority study, including girls aged 9-14 years who were randomized in a 1:1 ratio to receive 2 doses at months 0 and 6 (n = 301) or 3 doses at months 0, 1 and 6 (n = 304); girls aged 15-17 years (n = 149) and women aged 18–26 years (n = 225) who received 3 doses of the vaccine, were invited to participate in follow-up to 30 months post vaccination (NCT03206255). Serum samples were collected at months 18 and 30, and anti-HPV-16/18 IgG antibodies were measured by enzyme-linked immunosorbent assay. Serious adverse events (SAEs) occurred from month 7 through month 30 were recorded. At month 30, in the per-protocol set, all participants remained seropositive, except for one girl in the 9-14 years (2 doses) group who seroconverted to negative for HPV-18. HPV-16 and HPV-18 antibody levels were higher in girls aged 9-17 years who received 3 doses (125.3 and 60.2 IU/ml) than in women aged 18-26 years who received 3 doses (72.6 and 28.3 IU/ml), and those in girls aged 9-14 years who received 2 doses (73.2 and 24.9 IU/ml) were comparable to those in women aged 18-26 years who received 3 doses. No SAEs were reported to be causally related to vaccination. The E. coli-produced bivalent HPV-16/18 vaccine is safe and induces persistent protective antibodies for up to 30 months after vaccination in girls aged 9-17 years receiving 2 or 3 doses.